Analysis of Smartphone Application Mastery in Distance Learning for Deaf Children in Secondary School - Hudzaifah Hudzaifah; Muhammad Akhyar; Siti S Fadhilah (JURNAL PENDIDIKAN DASAR, 2021)
Abstract: Distance learning is a learning model that is applied as one of the policies of the world government in the field of education to break the chain of the spread of the covid-19 virus. Many problems occur during distance learning, including in special education, one of which is deaf children, where deaf children have barriers in communicating but must follow learning without meeting in person in the classroom. This study aims to find out what information technology is most mastered by deaf children as a means of supporting distance learning. This research was conducted on deaf children at the high school level in extraordinary schools that during the covid 19 pandemic the school implemented an online learning system. This study uses descriptive analysis with the questionnaire filling method. Data collection is done by disseminating questionnaires containing questions related to the mastery of applications on smartphones aimed at deaf children. Furthermore, the data is analyzed using inductive and thematic analytics. Dai this research can be known that from the use of Whatsapp Application as a means of communication used to receive distance learning materials is 94.74%, zoom meeting application mastery rate 0.00%, then youtube application mastery level in receiving information 100.00%. And the most preferred time for deaf children to learn is free, which is 65.79%. So it can be concluded that the smartphone application that is most mastered by deaf children in high school in learning and receiving information is a Youtube application and the preferred time for deaf children in learning is free or unspecified. Keywords: Mastery of Smartphone Applications; Deaf Children; Distance Learning